Gut microbiota in perioperative neurocognitive disorders: current evidence and future directions - Sun, Yan; Wang, Kexin; Zhao, Weiliang (Frontiers in Immunology, 2023)
Perioperative neurocognitive disorders (PND) is a common surgical anesthesia complication characterized by impairment of memory, attention, language understanding and social ability, which can lead to a decline in the quality of life of patients, prolong the hospitalization period and increase the mortality rate. PND has a high incidence rate, which has a great impact on postoperative recovery and quality of life of patients, and has caused a heavy economic burden to society and families. In recent years, PND has become an important public health problem. The high risk population of PND is more prone to gut microbiota imbalance, and gut microbiota may also affect the inflammatory response of the central nervous system through the microbiota-gut-brain axis. Meanwhile, Neuroinflammation and immune activation are important mechanisms of PND. Regulating gut microbiota through probiotics or fecal bacteria transplantation can significantly reduce neuroinflammation, reduce the abnormal activation of immune system and prevent the occurrence of PND. This review summarizes the research progress of gut microbiota and PND, providing basis for the prevention and treatment of PND.